New method for quantitatively characterizing emulsifying ability of oil displacement agents - ZOU Jirui; YUE Xiang’an; LI Xiaoxiao; SHAO Minglu; YANG Zhiguo; AN Weiqing (Youqi dizhi yu caishoulu)
The emulsifying ability of oil displacement agents plays a crucial role in the chemical flooding process， but the quantitative characterization of emulsifying ability remains unsolved. In response to this challenge， this paper presented a new method for quantitatively characterizing the emulsifying ability through emulsification of oil displacement agent-crude oil systems induced by rotating fluid. The method determined the experimental parameters （emulsification coefficient） characterizing the emulsifying ability of oil displacement agents by plotting the dynamic curve of emulsification oil rate at different rotational speeds. The emulsification coefficient fully characterized the initial rotational speed of emulsification， initial emulsification oil rate， and emulsification speed of oil displacement agents with crude oil and accurately distinguished and compared the differences in emulsifying ability caused by changes in the mass fraction of the oil displacement agent， type of oil displacement agent， and properties of the crude oil. By comparing the emulsification coefficients， it was found that AEO9 had the highest emulsification coefficient （1.184）， while SDS had the lowest emulsification coefficient （0.320）. The emulsifying ability of the oil displacement agents for CQ crude oil in descending order was as follows： AEO9＞SDBS＞SCS＞Na2CO3＞AEO5＞SDS. As the mass fraction of the oil displacement agent increased， the emulsification coefficient increased， indicating an enhanced emulsifying ability. The emulsifying ability of the oil displacement agents was also influenced by the properties of the crude oil. Due to the higher content of active components in SL crude oil， the emulsifying ability of the oil displacement agents is greater for SL crude oil than for CQ crude oil. In addition， the results of co-injection experiments involving surfactants and crude oil in porous media， as well as surfactant flooding experiments， indicate that oil displacement agents with higher emulsification coefficients exhibit stronger in-situ emulsifying ability in porous media. Therefore， using the emulsification coefficient as a parameter to characterize and evaluate the emulsifying ability of oil displacement agents is reasonable.